Shade Response of common Rainfed Intercrops of Coconut part III-Vegetables - Krishnankutty N K (Department of Agronomy, College of Horticulture, 1983)
A field experiment was conducted at the College of Horticulture, Vellanikara during 1982-83 to study the shade response of five common vegetable crops for assessing their suitability for intercropping in coconut gardens. The experiment was laid out in randomized block design with four levels of shade and five replications. The study revealed that bhindi, amaranthus, clusterbean and vegetable cowpea are unsuitable for intercropping as they are highly ‘shade sensitive’. Brinjal may be suitable for intercropping only in situations of ample light infiltration as it is ‘shade tolerant’. Photosynthetic mechanism appears to have a decisive role on the shade response of all these crops except brinjal in which translocation differences seem to be responsible. In all the crops there was branching suppression because of shading. The contents of total chlorophyll and its components were significantly increased by shading in all the crops. The contents of nitrogen and phosphorus were not affected by shading in any crop. But in the case of brinjal, bhindi and vegetable cowpea there was increase in potassium content due to shading. In general, the uptake of nutrients followed the trend of dry matter accumulation.